Perilaku Perjalanan Kota Makassar Selama Masa Pandemi Covid-19 - Nurul Ilmi Amaliyah (Syntax Idea)
The Covid-19 pandemic is a new phenomenon that has an impact on the whole world, including Indonesia. The rapid transmission of the virus prompted the government to issue regulations on limiting physical activity. This restriction policy has an impact not only on the health sector but also occurs in various other sectors such as the economy, education and transportation. Restrictions by the government and public concern about the Covid-19 virus resulted in a decrease in daily routines. People switch to using technology to meet their daily needs, for example for work purposes. This research specifically wants to see and measure the influence of work from home activities on travel behavior during the Covid-19 pandemic. This influence is measured using the Structural Equation Modeling Partial Least Square (SEM-PLS) quantitative analysis to see the impact of exogenous variables on endogenous variables through variables work from home that are composed of certain constructs as a whole. The results of the study show changes and influences between work from home activities and travel behavior after it occurred during the Covid-19 pandemic.